ANSIETAS DAN MEKANISME PERTAHANAN DALAM NOVEL NAMAKU ALAM 1 KARYA LEILA S. CHUDORI MENURUT TEORI PSIKOANALISIS - Munyati, Fathiyyah; Priyadi, Antonius Totok; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This research aims to describe anxiety and defense mechanisms in the novel Namaku Alam 1 by Leila S. Chudori and its implementation in Indonesian language teaching. The study employs a descriptive method with a qualitative research approach. The approach used is literary psychology based on Sigmund Freud's psychoanalytic theory. The research data consist of excerpts, phrases, sentences, and paragraphs. Data collection techniques involve documentary study. The data collection tool is the researcher themself, who serves as the key instrument in this research, along with the use of books, note cards, writing tools, and markers. The results of the study show that objective anxiety in this novel is experienced by the characters Yu Kenanga, Alam, Bu Warsih, and Bimo, while neurotic anxiety is found in the characters Ibu and Alam. The defense mechanism of rationalization occurs with a substitute motive to cover up the real motive, while the defense mechanism is employed to protect oneself, ultimately leading to self-destruction. The teaching module is prepared for the Indonesian language subject, phase F, grade XII in senior high school.